Learned switch readiness via concurrent activation of task sets: Evidence from task specificity and memory load. - Nack, Corey A.; Yu-Chin, Chiu (Memory & Cognition, 2024)
Cognitive flexibility increases when switch demands increase. In task switching experiments, repeated pairing of flexibility-demanding situations with specific contexts leads subjects to become more prepared to adapt to changing task demands in those contexts. One form of such upregulated cognitive flexibility has been demonstrated with a list-wide switch probability (LWSP) effect, where switch costs are smaller in lists with frequent switches than in lists with rare switches. According to a recent proposal, the LWSP effect is supported by a concurrent activation mechanism whereby both task rules are kept available simultaneously in working memory. We conducted four experiments to test two key features in this concurrent activation account of LWSP effects. First, we asked whether the LWSP effects are limited to only the trained tasks, and second, we asked whether concurrent working memory load would reduce the LWSP effects. In Experiment 1, we replicated and extended previous findings that the LWSP manipulation modulates both performance (switch costs) and voluntary switch rates, indicating that context-driven increases in flexibility are generalizable so long as the task-sets remain the same. Results of Experiments 2 and 3 showed that novel tasks do not benefit from the concurrent activation of the two other tasks, suggesting that the LWSP effect is task specific. Experiment 4 showed that holding additional information in working memory reduces the LWSP effect. While these findings support the hypothesis of concurrent activation underlying the increased flexibility in the LWSP effect, caveats remain; additional research is needed to further test this account.